Pengembangan Media Komik Interaktif Cerita Mbojo Berbasis Gerakan Literasi Sekolah untuk Meningkatkan Minat Baca Siswa - Fatimah, Nunung; Ningsyih, Surya (Lembaga Penelitian dan Pendidikan Mandala, 2021)
Reading is part of literacy in the lower grades carried out at school. At the elementary school level, literacy activities are the starting point for understanding other sciences. The success of the early stages is crucial for advancing to the next level. Effective literacy teaching in the early grades needs to pay attention to the learning environment and materials that suit the needs of students so that researchers are interested in conducting development research in this study specifically for low-grade students and for the place of research that is carried out at SDN Sari Kalampa. The development of interactive comic media for the Mbojo story based on the school literacy movement to increase students' reading interest carried out at SDN Sari Kalampa, Woha District, Bima Regency is very necessary. The purpose of this study is to find out the importance of using or developing a comic medium for the Mbojo story where this media will be reading material that aims to increase literacy activities. The results showed that the learning media for interactive comics based on the mbojo story based on the school literacy movement could increase students' reading interest with the average score of student responses being which was included in the